Instability of cylindrical relativistic electron beam, propagating in plasma - Balakirev, V.A.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2011)
The new mechanism of instability development of relativistic electron beam of finite radius in plasma has been considered. Two-dimensional linear theory of this instability has been constructed. As a result of this theory the frequencies of excited waves and growth rates of their excitation have been derived. 2.5-numerical simulation of nonlinear stage of instability development and bunching of relativistic beam has been performed. The possibility has been shown to use of this mechanism of instability for formation of train of short relativistic bunches, used in wakefield method of electron acceleration. Розглянутий новий механізм нестійкості радіально обмеженого релятивістського електронного пучка в плазмі. Збудовано двовимірну лінійну теорію цієї нестійкості, в результаті якої знайдені частоти збуджуваних хвиль та інкременти їх зростання. Проведено 2,5-вимірне числове моделювання нелінійної стадії розвитку нестійкості та групування релятивістського пучка. Показано можливість використання цього механізму нестійкості для отримання послідовності коротких релятивістських згустків, яка використовується в кільватерному методі прискорення. Рассмотрен новый механизм неустойчивости радиально ограниченного релятивистского электронного пучка в плазме. Построена двумерная линейная теория этой неустойчивости, в результате которой найдены собственные частоты возбуждаемых волн и инкременты их нарастания. Проведено 2,5-мерное численное моделирование нелинейной стадии развития неустойчивости и степени группировки релятивистского пучка. Показана возможность использования этого механизма неустойчивости для получения последовательности коротких релятивистских сгустков, используемой в схеме кильватерного метода ускорения.